2018
DOI: 10.2147/opth.s164195
|View full text |Cite
|
Sign up to set email alerts
|

Changes in choroidal thickness and volume are related to urinary albumin excretion in type 2 diabetic patients without retinopathy

Abstract: PurposeTo evaluate choroidal thickness and volume in patients with type 2 diabetes and microalbuminuria using spectral-domain optical coherence tomography.MethodsWe recruited 37 diabetic patients without diabetic retinopathy (18 normoalbuminuric and 19 microalbuminuric) and 21 healthy controls. Choroidal thickness and volume were mapped using the automated Early Treatment Diabetic Retinopathy Study grid and a topographic map of thickness was generated manually. Choroid was also measured at 10 locations under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Farias et al studied type 2 diabetes patients with no or mild DR and found a thinner subfoveal and temporal choroid CT in the microalbuminuric groups (when compared with normoalbuminuric) and a thinner subfoveal, temporal, and nasal CT in the microalbuminuric group when compared with controls [24]. Farias observed that mean subfoveal and temporal CT was significantly reduced in the microalbuminuric group when compared with normoalbuminuric [12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Farias et al studied type 2 diabetes patients with no or mild DR and found a thinner subfoveal and temporal choroid CT in the microalbuminuric groups (when compared with normoalbuminuric) and a thinner subfoveal, temporal, and nasal CT in the microalbuminuric group when compared with controls [24]. Farias observed that mean subfoveal and temporal CT was significantly reduced in the microalbuminuric group when compared with normoalbuminuric [12].…”
Section: Discussionmentioning
confidence: 99%
“…Poor control of factors influencing CT could be responsible for the conflicting results in the literature: axial length and refractive error, diurnal variation of CT, age (there is a decreased of subfoveal CT of approximately 3 microns per year of age), dehydration, and other systemic disease, that can affect choroidal vasculature like systemic hypertension [12,19,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations